The role of the private and public sector in human capital formation - Rainer Thiele (Intereconomics, 1997)
While there are strong equity and efficiency reasons for subsidizing education in developing countries, the prevailing dominance of governments in the financing and provision of educational services can be questioned. There is some evidence supporting the conclusion that a partial cost recovery through user fees may reduce the rationing of services which is still a pressing problem in many low-income countries, and that private providers tend to be more cost-efficient than their public counterparts.
Keywords: 330; Humankapital; Bildungsfinanzierung; Theorie; Welt